Quantification of methylcitrate in dried urine spots by liquid chromatography tandem mass spectrometry for the diagnosis of propionic and methylmalonic acidemias - Al Dhahouri, Nahid; Langhans, Claus-Dieter; Al Hammadi, Zalikha; Okun, Jürgen G.; Hoffmann, Georg F.; Al-Jasmi, Fatma; Al-Dirbashi, Osama Y. (Clinica chimica acta, 2018)
Accumulation of methylcitrate is a biochemical hallmark of inborn errors of propionate metabolism, a group of disorders that include propionic acidemia, methylmalonic aciduria and cobalamin defects. In clinical laboratories, this analyte is measured without quantification by gas chromatography mass spectrometry as part of urine organic acids. Here we describe a simple, sensitive and specific method to quantify methylcitrate in dried urine spots by liquid chromatography tandem mass spectrometry. Methylcitrate is extracted and derivatized with 4-[2-(N,N-dimethylamino)ethylaminosulfonyl]-7-(2-aminoethylamino)-2,1,3-benzoxadiazole in a single step. A derivatization mixture was added to 3.2mm disc of dried urine spots, incubated at 65°C for 45min and 4μl of the reaction mixture were analyzed. Separation was achieved on C18 column with methylcitrate eluting at 3.8min. Intraday and interday imprecision (n=17) were ≤20.9%. The method was applied on dried urine spots from established patients and controls. In controls (n=135), methylcitrate reference interval of 0.4-3.4mmol/mol creatinine. In patients, methylcitrate ranged between 8.3 and 591mmol/mol creatinine. Quantification of methylcitrate provides important diagnostic clues for propionic acidemia, methylmalonic aciduria and cobalamin disorders. The potential utilization of methylcitrate as monitoring biomarker of patients under treatment and whether it correlates with the clinical status has yet to be established.
Gesehen am 27.04.2020